Acceptability of local food-based noodles krokot flour (Portulaca plerace l.) porang flour (Amorphophallus muelleri blume) and breadfruit flour (Artocarpus Altilis) - Widyasari R.A. Hangesti Emi; Risqullah Nur Rifqi (E3S Web of Conferences)
The use of wheat flour which continues to increase every year makes the number of imported wheat as the basic ingredient for making wheat flour continue to grow, to reduce the number of imports gluten can be made by developing local food commodities that can be processed into flour products. Local food commodities. Local food commodities that can be made into flour products are purslane plants, porang tubers, and breadfruit. Noodles are widely favored as a substitute for rice, the basic ingredient of noodles is wheat flour noodles, namely multipurpose wheat flour, which can be replaced with local food commodities, namely local flour products of purslane flour, porang flour, and breadfruit flour. This experimental research uses primary data from organoleptic test results and chemical tests of super noodles. The protein, water, and ash test results do not follow SNI, namely Protein (2.99g) while in SNI (2987: 2015) wet noodle protein is 6%. Water content (79.83g) max 65% and ash content (0.48g) max 0.05 is unsuitable for carbohydrates and fat that have met SNI. The results of the organoleptic test showed that this super noodle was acceptable to the panelists with an average value of 3.69 from 5 parameters and this response is expected to be an alternative for the community to use local food as a substitute for wheat flour in noodle processing up to 50%.